Resveratrol-loaded metal-organic framework for mitochondria-targeted amplified CO gas therapy - Wang, Fengqin; Jiang, Yinfang; Wang, Yang (Frontiers in Chemistry, 2025)
Carbon monoxide (CO) based gas therapy has recently garnered significant attention due to its remarkable therapeutic effects for various major diseases. However, the primary challenge in gas therapy is the effective delivery of gas prodrug to targeted sites, as well as achieving precise spatial-temporal control over their release behavior. In this work, we provide a facile method to design ROS-responsive and mitochondrial targeting CO-delivery nanoplatform, based on the thiol-functionalized metal-organic framework (MOF), abbreviated as UiO-66-SH, incorporating the drug resveratrol (RES) for combined tumor therapy. After endocytosis by tumor cells and localization within the mitochondria, UiO@FeCO@RES was decomposed by ATP to release RES and generate CO gas via a Fenton-like reaction between hydroxyl radicals (·OH) and FeCO. RES acts as an ATPase inhibitor, disrupting the metabolism of the respiratory chain in tumor cell and thereby facilitating ATP-blocked metabolic therapy. In vitro experimental results demonstrate that the combination therapy, involving both RES drug and CO gas therapy, exhibits a synergistic effect against cancer cells. This synergistic strategy has endowed UiO@FeCO@RES as a promising material for biomedical applications.